Preservation of map archives in the National Mapping and Resource Information Authority (NAMRIA) - Go, Chatty Mae M.; Rey, Emma M.; National Mapping and Information Resource Authority (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Map is part of our history. It is a vital document that serves as a record of past events and landscapes. It is very important to study how to properly preserve it to prolong its life for future researches. It is in this light that this study focused on the preservation of map archives in the National Mapping and Information Resource Authority (NAMRIA).
The two divisions of NAMRIA namely: Information Services Division and Land Classification Division was the subject of the study. The personnel in-charge was surveyed. The survey questionnaire was sub-divided into four parts: (1) information about the institution; (2) preservation practices; (3) security; and (4) preservation problems and needs.
The data gathered from the survey questionnaires and interviews revealed that: (a) there is no preservation program for maps in NAMRIA; (b) the maps of NAMRIA do not have the ideal storage environment for prolonged preservation; (c) the physical security of the map collection is not enough; (d) there is lack of trained and knowledgeable personnel who can perform preservation to the materials; and (e) support from the management and budget allocation are definitely lacking.
Recommendations included allocation of a bigger budget, basic training on preservation of maps of personnel, presence of a manual or handbook, proper storage for maps, establishment of a centralized archive and further study about map archives.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Map collections -- Conservation and restoration -- Philippines; Archival materials -- Conservation and restoration -- Philippines